Targeting Cytokinin Homeostasis in Rapid Cycling Brassica rapa with Plant Growth Regulators INCYDE and TD-K - van Voorthuizen, Matthew J; Nisler, Jaroslav; Song, Jiancheng; Spíchal, Lukáš; Jameson, Paula E (Plants (Basel, Switzerland), 2020)
Modifying the cytokinin content in plants is a means of improving plant productivity. Here, we report the development and biological activity of compound TD-K (1-(furan-2-ylmethyl)-3-(1,2,3-thiadiazol-5-yl)urea)which is related to thidiazuron. TD-K-which exhibited extremely high antisenescence activity in the wheat leaf bioassay-and INCYDE (2-chloro-6-(3-methoxyphenyl)aminopurine)-a plant growth regulator reported to inhibit cytokinin oxidase/dehydrogenase (CKX), an enzyme involved in the degradation of the plant hormone cytokinin-were selected for investigation of their effects on the model plant Rapid Cycling Brassica rapa (RCBr). We monitored the expression of BrCKX and isopentenyl transferase (BrIPT), which codes for the key cytokinin biosynthesis enzyme, in developing leaves following INCYDE and TD-K application. Growth room experiments revealed that INCYDE increased RCBr seed yield per plant, but only when applied multiple times and when grown in 5 mM KNO3. Expression in control leaves showed transient, high levels of expression of BrCKX and BrIPT at true leaf appearance. Following INCYDE application, there was a rapid and strong upregulation of BrCKX3, and a transient downregulation of BrIPT1 and BrIPT3. Interestingly, the upregulation of BrCKX3 persisted in a milder form throughout the course of the experiment (16 days). TD-K also upregulated BrCKX3. However, in contrast to INCYDE, this effect disappeared after two days. These results suggest that both compounds (CKX inhibitor and cytokinin TD-K) influenced cytokinin homeostasis in RCBr leaves, but with different mechanisms.
Keywords: thidiazuron; isopentenyl transferase; CKX; cytokinin; cytokinin oxidase/dehydrogenase; IPT; INCYDE; TD-K